Does meiotic drive alter male mate preference?. (20th October 2019) - Finnegan, Sam Ronan; Nitsche, Leslie; Mondani, Matteo; Camus, M Florencia; Fowler, Kevin; Pomiankowski, Andrew
Abstract: Male mate preferences have been demonstrated across a range of species, including the Malaysian stalk-eyed fly, Teleopsis dalmanni . This species is subject to sex-ratio (SR), an X-linked male meiotic driver, which causes the dysfunction of Y-sperm and the production of all-female broods. While there has been work considering female avoidance of meiotic drive males, the mating decisions of drive-bearing males have not been considered previously. Drive males may be less able to bear the cost of choice as SR is associated with a low-frequency inversion that causes reduced organismal fitness. Drive males may also experience weaker selection for preference maintenance if they are avoided by females. Using binary choice trials, across two experiments, we confirmed male preference for large (fecund) females but found no evidence that the strength of male preference differs between drive and standard males. We showed that large eyespan males displayed strong preference for large females, whereas small eyespan males showed no preference. Taken together, these results suggest that, even though meiotic drive is associated with lower genetic quality, it does not directly interfere with male mate preference among available females. However, as drive males tend to have smaller eyespan (albeit only ~5% on average), this will to a minor extent weaken their strength of preference. Lay Summary: Meiotic drive is a selfish genetic element that kills half a male's sperm and reduces survival. Despite this, male stalk-eyed flies carrying meiotic drive exert strong mating preferences for large females, just like wildtype males. Male mate preference is unaffected by the loss in fitness caused by meiotic drive. This outcome reflects the large benefits of mate choice (large females are more fecund), and that males can choose without much cost.